Liver transplantation in 100 children: Cambridge and King's College Hospital series. Issue 6824 (15th February 1992) - Salt, A.; Noble-Jamieson, G.; Barnes, N. D.; Mowat, A. P.; Rolles, K.; Jamieson, N.; Johnston, P.; Friend, P.; Calne, R. Y.
Abstract : OBJECTIVE--To review the results of the Addenbrooke's and King's College Hospital children's liver transplantation programme. DESIGN--Retrospective analysis of the first 100 children to receive liver grafts at Addenbrooke's Hospital, Cambridge, from December 1983 to March 1990. SETTING--Addenbrooke's Hospital, Cambridge, and King's College Hospital, London. SUBJECTS--153 children assessed for liver transplantation, of whom 22 died before a donor became available and 31 were considered unsuitable. 100 children received grafts, of whom 27 had second grafts. RESULTS--One year actuarial patient survival was 71%, with 57% one year graft survival. In the last two years survival rates had improved considerably, with 86% of patients and 63% of grafts surviving for at least one year. Sixty five children were alive 12 to 86 months after transplantation; 63 were well and leading normal active lives and 56 had entirely normal liver function. Children's growth and development were essentially normal, with many showing remarkable catch up growth. CONCLUSIONS--Liver transplantation offers children with terminal liver disease a high chance of a return to full quality life and normal development. Improved surgical and medical care have progressively improved survival. The timing of transplantation is critical but has been constrained particularly by the availability of donors and resources.